2005
DOI: 10.1111/j.1365-2362.2005.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Paradox of simultaneous intestinal ischaemia and hyperaemia in inflammatory bowel disease

Abstract: This review has focused on evidence regarding intestinal perfusion of inflammatory bowel disease (IBD). Basic investigation has defined an altered microvascular anatomy in the affected IBD bowel, which corresponds with diminished mucosal perfusion in the setting of chronic, long-standing inflammation. Diminished perfusion is linked to impaired wound healing, and may contribute to the continued refractory mucosal damage, which characterizes IBD. Alterations in vascular anatomy and physiology in IBD suggests add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 153 publications
(192 reference statements)
4
39
0
Order By: Relevance
“…40) It has been reported that HIF-1α is overexpressed in colitis affected human and murine colon tissues. 13,41) In agreement with previous observations, HIF-1α was found to be elevated in the DSS group, but CA was found to reduce this increase, not to the same extent as SFZ. These results indicate that the inflammation observed in our DSS model is the result of both COX-2 and HIF-1α mediated response and that the inhibition of inflammatory response by CA is effective against both inflammatory molecules.…”
Section: Discussionsupporting
confidence: 81%
“…40) It has been reported that HIF-1α is overexpressed in colitis affected human and murine colon tissues. 13,41) In agreement with previous observations, HIF-1α was found to be elevated in the DSS group, but CA was found to reduce this increase, not to the same extent as SFZ. These results indicate that the inflammation observed in our DSS model is the result of both COX-2 and HIF-1α mediated response and that the inhibition of inflammatory response by CA is effective against both inflammatory molecules.…”
Section: Discussionsupporting
confidence: 81%
“…A number of studies have implicated the occurrence of hypoxia in mucosal inflammatory diseases such as IBD [12]. Surgical specimens from patients with IBD have revealed prominent hypoxia-inducible factor (HIF)-1 and HIF-2 activation associated with increased vascular density in diseased areas [13].…”
Section: Hypoxia and Mucosal Inflammationmentioning
confidence: 99%
“…Surgical specimens from patients with IBD have revealed prominent hypoxia-inducible factor (HIF)-1 and HIF-2 activation associated with increased vascular density in diseased areas [13]. Other studies in humans have revealed that a number of microvascular abnormalities may contribute to diminished blood flow to the intestine in IBD, including the loss of endothelial nitric oxide generation and enhanced tissue vasoconstrictor production [12]. Moreover, Vascular endothelial growth factor-dependent angiogenesis appears to be an integral part of human IBD [14].…”
Section: Hypoxia and Mucosal Inflammationmentioning
confidence: 99%
“…A number of clinical and experimental studies showed oxygen deprivation of colonic epithelial cells in inflammatory bowel disease (IBD). 5,10,25,36 Moreover, prevention of hypoxia by heparin 37 or endothelin-1 receptor antagonist 38 significantly reduced the degree of mucosal injury and inflammatory response. In addition to endothelial damage and intravascular congestion, our present study demonstrated hypoxia in colonic surface epithelial cells that preceded the enhanced colonic EP.…”
Section: Endothelial Damage In Ulcerative Colitismentioning
confidence: 99%